2014
DOI: 10.5120/16821-6575
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Fault Detection of Analogue Circuits

Abstract: This paper presents a new testing approach for analogue circuits based on the digital signature analysis. In this paper, the efficient parametric fault detection approach for analogue circuits using the simulation environment is presented. This approach has three main parts, an analogue test pattern generator (ATPG), an analogue test response compactor (ATRC), and an analogue circuit under test (ACUT) model, build in the PSpice circuit simulator. The proper ATPG is designed to sweep the applying sinusoidal fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Compared to GA-SVM and PSO-SVM, Yang Dalian showed that the artificial bee colony algorithm could obtain a higher performance both in time consumption and recognition rates of gearbox faults [40] . Recently, Bayesian Optimization (BO) became a popular choice amongst researchers because it calculates a prior belief about behavior of the hyperparameters and then searches the parameter space by accomplishing and updating it based on its current measurement [2,15] . In general, intelligence algorithm optimization can attain relatively good results, but cannot avoid multiple iterations in determination of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to GA-SVM and PSO-SVM, Yang Dalian showed that the artificial bee colony algorithm could obtain a higher performance both in time consumption and recognition rates of gearbox faults [40] . Recently, Bayesian Optimization (BO) became a popular choice amongst researchers because it calculates a prior belief about behavior of the hyperparameters and then searches the parameter space by accomplishing and updating it based on its current measurement [2,15] . In general, intelligence algorithm optimization can attain relatively good results, but cannot avoid multiple iterations in determination of parameters.…”
Section: Introductionmentioning
confidence: 99%